The Inner Conflict Reflected in the Main Character of Papang in Kanittha Kwanyu’s The Comments (2021) - Edi Sumarsono; Latifah Dwi Ariyani (Metaphor, 2023)
This research aims to analyze how inner conflict occurs and what types of inner conflict appear in the main characters in The Comments (2021). There are two problem formulations that the researchers use in this study, first, How does Papang's inner conflict reflected in The Comments (2021) by Kanittha Kwanyu? Second, What kind of inner conflict does Papang go through in The Comments (2021) by Kanittha Kwanyu? Researchers used qualitative methods to examine the problem. The theory and approach that researchers use are Freud's Psychoanalysis and Theory of Inner Conflict. This research also includes data collection procedures and data analysis procedures. The results of this research are, first, the causes of inner conflict in the main character, and what types of inner conflict arise from the first episode to the fifth episode.